The Influence Of Punishment And Reward On Employee Work Effectiveness At Muhammad Taufik Kiemas Airport, Krui, Lampung - Rano Rumansyah; Emila Sholiha; Markus Markus (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the effect of Punishment on employee work effectiveness at Muhammad Taufik Kiemas Airport, KRUI, Lampung. To determine the effect of Rewards on employee work effectiveness at Muhammad Taufik Kiemas Airport, KRUI, Lampung. To determine the joint effect of Punishment and Rewards on employee work effectiveness at Muhammad Taufik Kiemas Airport, KRUI, Lampung. The sample in this study was all 39 employees at Muhammad Taufik Kiemas Airport, KRUI, Lampung. Therefore, the sampling technique used in this study was the census method. The census method involves data collection involving the entire population. The results showed that Punishment significantly influenced employee work effectiveness at Muhammad Taufik Kiemas Airport, KRUI, Lampung. Rewards significantly influenced employee work effectiveness at Muhammad Taufik Kiemas Airport, KRUI, Lampung. Punishment and Rewards significantly influenced employee work effectiveness at Muhammad Taufik Kiemas Airport, KRUI, Lampung.